The Herbal Cocktail GSYJ Attenuated Airway Inflammatory Cell Infiltration in a Chronic Asthmatic Mouse Model. (25th February 2021) - Chiang, Chung-Jen; Chang, Shu-Lun; Lin, Li-Jen
Abstract : This study explored the potential therapeutic efficacy of GSYJ in attenuating asthma symptom severity and aimed to determine the immunomodulatory mechanism of GSYJ. A mouse model of chronic asthma induced by repeated Dermatophagoides pteronyssinus (Der p) challenge was established. In addition, 30 minutes before Der p challenge, the mice were orally administered GSYJ (1 g/kg). The mice were sacrificed to evaluate inflammatory cell infiltration, collagen deposition in the lung, total IgE in serum, and expression profiles of various cytokines in bronchoalveolar lavage fluid (BALF) and various genes in lung tissue. Furthermore, 30 minutes after the addition of GSYJ to RAW264.7 cell cultures, 100 ng/ml LPS was added to evaluate the effect of the drug on the LPS-induced expression of genes, proteins, and transcription factors. GSYJ may regulate transcription factors (cJUN/IRF3/NF- κ B) to decrease the expression of IL-1 β, IL-6, RANTES, and iNOS in macrophages and affect the IL-12, IFN- γ, IL-5, and IL-6 levels in the BALF of mice to relieve asthma symptoms, such as inflammatory cell infiltration, hyperresponsiveness, and increased serum total IgE levels. Therefore, GSYJ has the potential to be developed into a drug treatment for chronic asthma.